ANALISIS KUALITAS KARYAWAN TERHADAP KEPUASAN PELANGGAN CV RAJA PROPERTY BANDAR LAMPUNG - Citra Savitri (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
The problems in the CV. Raja Property Bandar Lampung is the quality of the employeeshave not been effective in terms of treating damaged housing facilities and promotion the companiesare less intense in marketing products and services. Other than that, costumer satisfaction is on thelow level on the facilities and infrastructure in the CV. Raja Property Bandar Lampung. The purposeof this research is to analyze and describe the quality of the customer's employee to customersatisfaction CV. Raja Property Bandar Lampung.The result of the research that the level of customer satisfaction is very satisfied with the goodservice with a percentage of 53.33%, while the level of quality of service is very satisfied with thepercentage of 46.67%, satisfied with good service 53.33 % and less satisfied with the service of alow 46.67%.